2012
DOI: 10.1208/s12249-012-9875-3
|View full text |Cite
|
Sign up to set email alerts
|

Using USP I and USP IV for Discriminating Dissolution Rates of Nano- and Microparticle-Loaded Pharmaceutical Strip-Films

Abstract: Abstract. Recent interest in the development of drug particle-laden strip-films suggests the need for establishing standard regulatory tests for their dissolution. In this work, we consider the dissolution testing of griseofulvin (GF) particles, a poorly water-soluble compound, incorporated into a strip-film dosage form. The basket apparatus (USP I) and the flow-through cell dissolution apparatus (USP IV) were employed using 0.54% sodium dodecyl sulfate as the dissolution medium as per USP standard. Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…The majority of drug dissolution (>90%) was achieved using a biologically realistic volume of gastric medium (240 ml after 30 min). The design of the flow-through dissolution cell allows laminar and more homogeneous flow to be readily achieved due to the pressure drop imparted when beads are used (18). No drop in drug percentage occurs as the dissolved fraction was readily emptied from the flow cell, preventing drug accumulation in the dissolution medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of drug dissolution (>90%) was achieved using a biologically realistic volume of gastric medium (240 ml after 30 min). The design of the flow-through dissolution cell allows laminar and more homogeneous flow to be readily achieved due to the pressure drop imparted when beads are used (18). No drop in drug percentage occurs as the dissolved fraction was readily emptied from the flow cell, preventing drug accumulation in the dissolution medium.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been increasingly used to study release pattern from microsphere and film-based systems (17)(18)(19). It allows laminar flow, use of different sequences of dissolution media and continuous replenishing of drug saturated media with a fresh drug-free medium, hence limiting the risk of supersaturation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) (30), precision expresses the closeness of agreement between a series of measurements obtained from multiple sampling of same homogeneous sample under the prescribed conditions and is usually expressed as the variance, standard deviation, or coefficient of variation of a series of measurements. However, some previous studies reported high standard deviation values (represented in graphs points of drug release profiles) for in vitro drug release studies from nanostructured systems using the dialysis sac method (11) or different USP apparatus such as the apparatus IV (7,13). This way, taking into account the observed tendency for lower standard deviation in the drug release profiles achieving using the continuous-flow method compared to the conventional dialysis method, we may suggest that the continuous-flow apparatus proposed in this study is able to provide better data precision, compared to conventional dialysis sac method.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have proposed the use of different USP dissolution apparatus to assess the drug release profile from micro-or nanostructured systems such as apparatus I, II, and IV, showing their advantages and disadvantages (6,7,(13)(14)(15). Among the studies performed, the flow-through cell apparatus seems to be the best alternative to conduct in vitro release studies on dispersed systems due to its high discriminative power and to the fact that it can easily be converted in an automated process (7,13,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation